2018
DOI: 10.1039/c8ra08897g
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient in situ N-heterocyclic carbene palladium(ii) generated from Pd(OAc)2 catalysts for carbonylative Suzuki coupling reactions of arylboronic acids with 2-bromopyridine under inert conditions leading to unsymmetrical arylpyridine ketones: synthesis, characterization and cytotoxic activities

Abstract: The in situ prepared four component system Pd(OAc)2, 1,3-dialkylbenzimidazolium halides 2a–i and 4a–i, K2CO3 under CO atmosphere catalyses carbonylative cross-coupling reaction of 2-bromopyridine with various boronic acids to yield unsymmetrical arylpyridine ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…There are limited published articles on the palladium‐catalyzed carbonylative Suzuki–Miyaura coupling reactions of aryl bromides with aryl boronic acid 2,28,60–62 . For instance, the carbonylative Suzuki–Miyaura coupling reactions of aryl boronic acids with 2‐bromopyridine or aryl bromides have been associated with many shortcomings such as high catalyst loading, low yields, and low selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited published articles on the palladium‐catalyzed carbonylative Suzuki–Miyaura coupling reactions of aryl bromides with aryl boronic acid 2,28,60–62 . For instance, the carbonylative Suzuki–Miyaura coupling reactions of aryl boronic acids with 2‐bromopyridine or aryl bromides have been associated with many shortcomings such as high catalyst loading, low yields, and low selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the carbonylative Suzuki–Miyaura coupling reactions of aryl boronic acids with 2‐bromopyridine or aryl bromides have been associated with many shortcomings such as high catalyst loading, low yields, and low selectivity. In addition, these reactions need high in situ loading of phosphines 2,28,60,63 . To our knowledge, Pd(II)‐NHC complexes were not largely reported as catalysts in the carbonylative Suzuki–Miyaura coupling reactions of aryl bromides with boronic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Hamdi et al reported the use of N,N-substituted benzimidazole salts as ligands in the carbonylative Suzuki coupling reactions catalysed by in-situ generated NHC-Pd(II) catalysts (Scheme 16). [49] Aryl boronic acids were coupled with 2bromopyridine under inert conditions to form unsymmetrical aryl pyridine ketones under the optimized reaction conditions of 5 mol% of ligand, Pd(OAc) 2 (2.5 mol%) and K 2 CO 3 (2.0 mmol) in tetrahydrofuran (THF) at 110 °C under CO atmosphere (20 bar). Benzimidazoles with sterically hindered groups gave lower yields and the efficiency of the reaction was found to depend on the nature of the arylboronic acid, which influence the electronic properties of substances on catalytic reaction.…”
Section: Homogeneous Catalytic Systemsmentioning
confidence: 99%
“…N-heterocyclic carbene ligands have proven to be very useful for designing new metal complexes for catalysis. [38]. All of the benzimidazolium salts used as NHC precursors were prepared similarly by using the published procedures [39,40].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%